THE IMPLEMENTATION OF A FLIPPED CLASSROOM MODEL UTILIZING A SCIENTIFIC APPROACH AND FLIPBOOK MAKER E-MODULE TO IMPROVE STUDENT LEARNING OUTCOMES - Dewi Handayani; Endang Widi Winarni; Agus Sundaryono; Muhammad Lutfi Firdaus; Muzanip Alperi (Erudio Journal of Educational Innovation, 2021)
This research aimed to determine the influence of the flipped classroom model on students learning outcomes on the chemistry subject, particularly on electrolyte and non-electrolyte solutions. This research employed pre-experimental research and a one-group pre-test post-test design on one sample group. We used the method to compare pre-test and post-test results. This research was conducted in Public High School 9, Bengkulu City, Bengkulu Province, Indonesia. The population was 76 tenth graders of Mathematics and Natural Science Class. As many as 25 students of Class X-I were chosen as the samples using purposive sampling. The research instrument was pre-test and post-test, consisting of 10 questions to assess learning outcomes. We analyzed the average value of learning outcomes. The SPSS application was used to evaluate the normality, homogeneity, and hypotheses. The average pre-test score was 64.6, and the average post-test score was 87.8. Learning outcomes were normally and homogeneously distributed. The hypothesis testing produced a significance value of 0.000<0.05. Therefore, the flipped classroom model using a scientific approach and e-modules significantly affected the learning outcomes of the chemistry subject. The research result showed that the implementation of the flipped classroom model positively affected and improved the learning outcomes on the chemistry subject, particularly on electrolyte and non-electrolyte solutions.